Joint planning of energy storage site selection and line capacity expansion in distribution networks considering the volatility of new energy - Feifei, Xu; Xia, Pan; Bowei, Chen; Xiaoshuang, Li; Zhi, Nie; Miaoyong, Feng (Frontiers in Energy Research, 2024)
Under the coordinated operation of the transmission and distribution networks, the issue of downstream grid flow returning to the upstream grid is becoming increasingly prominent. This article proposes a process for joint planning of energy storage site selection and line capacity expansion in distribution networks considering the volatility of new energy. This technology uses CHk-means clustering calculations based on actual large-scale operation data of new energy sources to generate typical operating curves. Then, it finely constructs an objective function considering power transmission in the transmission-distribution network, abandonment of new energy, line limits, and energy storage construction. By introducing indicative constraints to the energy storage construction-related constraints, the optimization model achieves a non-iterative direct solution. The results of the constructed new energy high-penetration distribution network example IEEE Case33 show that the output solution of this model can effectively reduce the energy sent back from the distribution network to the main grid. Compared to optimization models that do not consider the integration of new energy sources, the output solution of this model can reduce the abandonment of new energy by at least 50%. It also avoids the numerical problems that may arise from iterative algorithms and logical transformation, demonstrating engineering application value.